The impact of simulated intra-abdominal movement on basic laparoscopic skills development: a feasibility study. - Klok, Jan-Willem; Rahimi, Masie; Hardon, Sem; Postema, Roelf; Bonjer, Jaap; Daams, Freek; Dankelman, Jenny; Horeman, Tim (Minimally Invasive Therapy & Allied Technologies, 2025)
Background: Laparoscopic surgery requires a complex set of motor skills. Currently, basic laparoscopic skills training is performed in a static environment, while intraoperatively, abdominal tissue is often moving. The aim of this study was to develop a dynamic training platform and evaluate its impact on laparoscopic skills acquisition in a box trainer. Methods: The Dynamic Laparoscopic Platform (DyLaP) includes a moving base which has been intergrated with the Lapron box trainer and the ForceSense objective measurement system. Dynamic training was evaluated in a comparative study where novices were divided into a static and dynamic training group, performing six training trials of a peg transfer task with the DyLaP. Afterwards, both groups performed a dynamic exam task. Task manipulation (force) and instrument efficiency (path length and time) were measured. Results: Participants (n = 12) exhibited a significant difference (p < 0.05) in time, path length, and maximum force between the static and dynamic groups in the first trial. Learning curves were most prevalent in the dynamic group. Conclusions: The DyLaP can be used to provide a challenging and realistic training environment. From the comparative peg transfer study, it can be concluded that dynamic training significantly affects laparoscopic skill acquisition. More research is needed to evaluate dynamic training effects in force-based training tasks.